Improving representation learning through variational autoencoding - Lin, S (2022)
Representation learning aims to distill useful knowledge from raw data and apply this knowledge to a wide range of applications. This ability to extract information that is useful not only for selected tasks but also generalizes to new settings is a key step towards artificial intelligence.